The Effect of Price Policy on Price Dynamics: Empirical Evidence in Indonesian Rice Market at Wholesale Level - Bayu Krisnamurthi; Anisa Dwi Utami (Universitas Muhammadiyah Yogyakarta, 2022)
As a major share expenditure for the poor, rice is attributed as a strategic food commodity in the Indonesian economy. For many decades, the Indonesian rice market has been intervened by the price regulation. The Indonesian government had set two types of rice price policies of 2016 and 2017 with the argument of price stabilization during the last five years. This study aimed to investigate the effect of price policies of 2016 and 2017 on the domestic price dynamics in the Indonesian rice market. This study used daily price series taken from the Cipinang Wholesale Rice Market in Jakarta within the period of October 1st, 2014, until February 12th, 2018 covering 10 rice varieties. The role of price policy on the price dynamics was evaluated by using a multivariate error correction model (MVECM). The empirical findings confirmed that generally, these price policies had different effects on the price dynamics which proposed different reactions from the different rice varieties both in magnitude and signs. The variations were also found regarding the short-run and long-run behavior. Generally, the findings suggested a relatively small elasticity of the policy on the prices.